Manpower Planning in the Professions - Stager, David; Meltz, Noah M. (Canadian Journal of Higher Education, 1977)
Manpower planning has been the subject of discussion and heated debate for more than a decade. Proponents have claimed that planning will enhance economic growth, particularly when it relates to professional and skilled manpower.1 Opponents have claimed that such planning distorts the market and will lead to excess supply or excess demand and in either case is costly in terms of economic resources. Our objective in this paper is to outline the general issues in manpower planning, briefly look at what is being done today in Canada, and then offer some suggestions concerning directions manpower planning might take. This paper is not intended to be a comprehensive review of the subject since other studies have gone into far more depth.3 Instead, we want to raise what we consider to be the major questions concerning how and what manpower planning is done.